STRATEGI PENGEMBANGAN BANK PAKAN SAPI DENGAN PENDEKATAN MODEL BISNIS KANVAS - Muhammad Akbar; Harianto Harianto; Nahrowi Nahrowi (Jurnal Agribisnis Indonesia, 2023)
Feed affects the reproductive cycle of cows,which has an impact on efforts to increase the population. The purpose of this research is to describe and improve the business model using the Business Model Canvas (BMC) approach and SWOT analysis to produce a new business model prototype for the Sepakat feed bank group. The procedure for collecting data in this study was in-depth interviews and focus group discussion (FGD). The results of this research show that the main elements that must be improved in the initial mapping of the business model in the agreed feed bank group are value propositions, channels, key activities, key resources, key partners, and revenue streams. The SWOT analysis illustrates that the strengths are well-mapped customers, abundant raw materials. The weaknesses are in the low quality of human resources in terms of maintenance of feed processing equipment, limited land, and the lack of superior forage varieties, processed feed production is not continuous, product distribution channels are not varied, and business capital restrictions. Opportunities that can be exploited are the development of new processed feed products, utilization of information technology and government support. The threats faced are dependence on one processed product and a climate dominated by a dry season. Improvement strategies carried out include creating new products (value proposition) using feed formulations based on availability, nutritional content, and prices of feed raw materials, utilizing various facilities for sales channels (channels) such as social media and BUMDes, establishing separate business units to manage feed banks (key activities), establishing superior foraging nurseries by utilizing land belonging to the Bima district government (key resources), establishing cooperative partnerships with financial institutions (key partners) and ensuring feed processing machines continue to function and operate to produce feed as a source of main income (revenue stream).